Fairness, Justice, and Language Assessment: The Role of Measurement: by McNamara, T., Knoch, U., and J., Fan, Oxford, Oxford University Press, 2019, 215 pp., $40.32 (paperback), ISBN 978-0-19-401708-4. Issue 3 (2nd July 2020) - Lin, Dunlai; Gao, Miao
ABSTRACT: This article reviews a recent book on the application of Rasch measurement in language assessment titled Fairness, Justice, and Language Assessment: The Role of Measurement . It provides a brief summary of the book and critiques its strengths and weaknesses.